Hubungan Antara Tingkat Pengetahuan Tentang Diet Hipertensi Dengan Kejadian Kekambuhan Hipertensi Lansia Di Desa Mancasan Wilayah Kerja Puskesmas I Baki Sukoharjo - Putri, Risanti Astika, H.M. Abi Muhlisin, SKM., M.Kep, Fahrun Nur Rosyid, S.Kep., M.Kep (2014)
Hypertension recurrence in village Mancasan Baki Sukoharjo is still high, whom 158 members of elderly posyandu, 82 members with hypertension. From 82 elderly, 35 the other recurrence hypertension between 5-7 times. The recurrence of hypertension was influenced by lack of knowledge of hypertension diet and influence to poor behavior hypertension diet. Research purposes is to know correlation between hypertension diet knowledge level with recurrence hypertension in Mancasan Village of Puskesmas I of Baki Sukoharjo. This study uses an analytical cross sectional study design sample research is all of members elderly posyandu who hypertension. Taking sample was using total sampling. Instrument research was using questionnaire and data of health blood pressure. Analysis data was use chi square test. Based on research that 18 respondents (22%) with good knowledge, 42 respondents(51,2%) fair, and 22 respondents (26,8%) with poor. frequency of Recurrence Hypertension that 23 respondents (28%) rapid, 35 respondents (42,7%) rarely and 24 respondents (29,3%) seldom. Based of chi square test with 2 =12,861 p-value 0.01, It concluded there was a correlation between hypertension diet knowledge level with recurrence hypertension in Mancasan village of Puskesmas I of Baki Sukoharjo. Conclusion this research that recurrence hypertension of elderly was caused elderly with lack hypertension diet, so it was influence to hypertension diet behavior. Its need to increase knowledge and social support to diet hypertension compliance